The Vermilionectomy and the Subsequent Lower Lip Reconstruction Were Introduced by Victor von Bruns and not by von Langenbeck or von Esmarch as Reported Previously. Issue 5 (May 2016) - Roldán, J. Camilo; Teschke, Marcus; Feinendegen, Dominik L.
Abstract : Summary: Vermilionectomy is an established procedure for the management of precancerous lesions of the lip and is often performed simultaneously with a lower lip resection for the treatment of a malignancy. The literature suggests that Dieffenbach or von Langenbeck or von Esmarch was the first to introduce this procedure. A systematic review of the German literature from the 19th century revealed that it was von Bruns who performed the vermilionectomy for the management of lip malignancies for the first time.